2021
DOI: 10.3390/life11101035
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Molecular Imaging (MRI/MRS/1H NMR) for Metabolic Information in Young Adults with Health Risk Obesity

Abstract: Background: Obesity or being overweight is a medical condition of abnormal body fat accumulation which is associated with a higher risk of developing metabolic syndrome. The distinct body fat depots on specific parts of the anatomy have unique metabolic properties and different types of regional excessive fat distribution can be a disease hazard. The aim of this study was to identify the metabolome and molecular imaging phenotypes among a young adult population. Methods: The amount and distribution of fat and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 69 publications
2
3
1
Order By: Relevance
“…Our study evaluated the strongest relationship between visceral fat and blood cholesterol (r = 0.834, p < 0.05) among the other ectopic fat relations. This finding is consistent with our in vivo study on young adult populations in which visceral fat had the most significant and strongest relationship to blood TG and HDL-C levels when compared to abdominal and subcutaneous lipids [ 35 ]. Meek et al also found that intra-abdominal adipocytes are less responsive to insulin’s anti-lipolytic actions, and that visceral adipose tissue-derived free fatty acid (FFA) may have more significance in vivo, reaching up to 40%.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our study evaluated the strongest relationship between visceral fat and blood cholesterol (r = 0.834, p < 0.05) among the other ectopic fat relations. This finding is consistent with our in vivo study on young adult populations in which visceral fat had the most significant and strongest relationship to blood TG and HDL-C levels when compared to abdominal and subcutaneous lipids [ 35 ]. Meek et al also found that intra-abdominal adipocytes are less responsive to insulin’s anti-lipolytic actions, and that visceral adipose tissue-derived free fatty acid (FFA) may have more significance in vivo, reaching up to 40%.…”
Section: Discussionsupporting
confidence: 92%
“…There was a similar conclusion in studies carried out on humans. This finding supports the idea that high visceral fat, especially in young obese people, could be a dyslipidemia-treated biomarker [ 35 ]. The health risks vary depending on the compartmental obesity, even in the same degree of obesity, and particularly in intra-abdominal obesity.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…A 3 × 3 × 3 cm 3 voxel will be manually placed at the right lobe of the liver (Couinaud lobe segment V-VIII), avoiding bile ducts, large vessels, focal lesions, and liver edges during the MRS scan. 23 After 5 min of the free-breathing scan, spectra will be obtained using the single-voxel point-resolved spectroscopy (PRESS) sequence. Spectral data will be exported as a raw dataset (p-file) for spectral analysis.…”
Section: Methodsmentioning
confidence: 99%